Spatiotemporal Parameters of Gait Among Adolescent Athletes with Concussion When Performing a Visuospatial Cognitive Task - Leah Lowe; Fernando Castillo; Melissa Allen; Michael Israel; Charlotte Yates (International Journal of Sports Physical Therapy)
# Background